Analisis Bauran Eceran Di Divisi Waserda Dalam Upaya Meningkatkan Partisipasi Anggota - Udayat Udayat; Bambang Nur Hidayat (PRISMAKOM, 2018)
Member Participation decreases at Waserda Division of Koperasi Keluarga Pegawai Institut Teknologi Bandung. It is seen from the progress of amount of members in 2016 and 2017 that decreased -1,04% and -1,98%. Then on progress of turnover of KKP ITB in 2017 decreases -1.17%. And it is seen from data of member participation of transaction service at Waserda Division of KKP ITB in 2017 decreases -18.48%. The last, it is also seen progress of income at Waserda Division of KKP ITB in last 2 years (2016 and 2017) decreases -2.93% and -5.42%. Based on those things, it is needed analysis to retailing mix that has been applied as the effort to fix it. With application of good retailing mix by Waserda Division of Koperasi Keluarga Pegawai Institut Teknologi Bandung, it is expected can increase member participation of cooperative that in the end can give direct economic benefit to members itself.